Peran Wayang dalam penyebaran ajaran Islam di Indonesia: Sebuah kajian sejarah dan budaya - Firdaus, Rubayyi (Maliki Interdisciplinary Journal, 2023)
This article discusses the role of wayang in spreading Islamic teachings in Indonesia, through historical and cultural studies. In compiling this article, the author of the article uses the literature study method, namely by searching and then collecting suitable and relevant sources. Wayang, as a traditional Indonesian performing art rich in symbolism, has played an important role as a medium for teaching Islamic values and messages to the public. Along with the history of the spread of Islam in Indonesia, wayang has become an effective medium for spreading Islamic teachings in an interesting and easy-to-understand way. At first, the stories in wayang performances were more dominated by Hindu and Mahabharata stories, but with the arrival of Islam, Islamic stories began to be introduced into wayang performances. In this study, we will trace the history of Islamic wayang in Indonesia, and the role of figures such as Sunan Kalijaga in introducing Islamic teachings through wayang stories by changing and adding characters in wayang as well as the philosophical meanings of each character. As a writer, he hopes that this article can provide deeper insight into the role of wayang in spreading Islamic teachings in Indonesia.